Journalistic discourse of freedom: A study of journalists’ understanding of freedom in the Czech Republic and Serbia - Rupar, Verica and Němcová Tejkalová, Alice and Láb, Filip and Seizova, Sonja (Journalism, 2021)
The idea of freedom plays a strong and important role among journalists in countries that have recently moved to democracy. In this article, we explore the relational nature of freedom and put forward an argument for more clarity in defining its meaning. We examine the values and experiences inscribed in journalistic discourses of freedom assuming that the ways of articulating freedom hold a key for understanding journalism practice. The article revises the question of freedom by focusing on the intersection between political and journalistic fields in two countries that moved from a one-party political system to political pluralism: the Czech Republic and Serbia. It seeks to give a perspective on understanding how concepts of freedom and autonomy work in Czech and Serbian journalistic discourse. The Worlds of Journalism Study’s data on journalists’ perception of political influences were used as a starting point, then a case study analysis of significant clashes between journalistic and political fields in recent years in both countries was applied. In 2014, both Czech and Serbian journalists declared that political factors had small influence on their daily work, but the situation has changed. Our case studies of recent developments in Serbia and the Czech Republic, show a striking discrepancy between what journalists perceive and what they know.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDY0ODg0OTE5ODY4MDc1